How to be "In on the Finish" - National Paint, Varnish (Pamphlets corresponding to radio shows produced by the National Paint, Varnish and Lacquer Association, 1940)
Booklet corresponding to a radio broadcast program created by the National Paint, Varnish, and Lacquer Association. The booklet discusses how to care for wooden furniture. Describes veneers, staining, polish, and other coatings for preserving furniture. Provides tips and tricks for polishing a piece of wooden furniture. Includes small stylized illustrations throughout and decorated covers. The National Paint, Oil and Varnish Association, Inc. was formed in 1933 and was the national professional association representing all branches of the paint, oil, and varnish industries.
Keywords: Shellac; Furniture; Linseed oil; Oilseeds; Varnish and varnishing; Varnish industry; Furniture polishes; Furniture finishing